Overt and covert genetic causes of pediatric acute lymphoblastic leukemia - Stoltze, Ulrik; Junk, Stefanie V; Byrjalsen, Anna; Cavé, Hélène; Cazzaniga, Giovanni; Elitzur, Sarah; Fronkova, Eva; Hjalgrim, Lisa Lyngsie; Kuiper, Roland P; Lundgren, Louise; Mescher, Melina; Mikkelsen, Theis; et al. (Leukemia, 2025)
Pediatric acute lymphoblastic leukemia (pALL) is the most common childhood malignancy, yet its etiology remains incompletely understood. However, over the course of three waves of germline genetic research, several non-environmental causes have been identified. Beginning with trisomy 21, seven overt cancer predisposition syndromes (CPSs)-characterized by broad clinical phenotypes that include an elevated risk of pALL-were first described. More recently, newly described CPSs conferring high risk of pALL are increasingly covert, with six exhibiting only minimal or no non-cancer features. These 13 CPSs now represent the principal known hereditary causes of pALL, and human pangenomic data indicates a strong negative selection against mutations in the genes associated with these conditions. Collectively they affect approximately 1 in 450 newborns, of which just a minority will develop the disease. As evidenced by tailored leukemia care protocols for children with trisomy 21, there is growing recognition that CPSs warrant specialized diagnostic, therapeutic, and long-term management strategies. In this review, we investigate the evidence that the 12 other CPSs associated with high risk of pALL may also see benefits from specialized care - even if these needs are often incompletely mapped or addressed in the clinic. Given the rarity of each syndrome, collaborative international research and shared data initiatives will be crucial for advancing knowledge and improving outcomes for these patients.
Keywords: Genetic Predisposition to Disease; akutní lymfatická leukemie; Humans; genetická predispozice k nemoci; Precursor Cell Lymphoblastic Leukemia-Lymphoma; dítě; lidé; Child